On the Origin and Evolution of Microbial Mercury Methylation. (23rd March 2023) - Lin, Heyu; Moody, Edmund R R; Williams, Tom A; Moreau, John W
Abstract: The origin of microbial mercury methylation has long been a mystery. Here, we employed genome-resolved phylogenetic analyses to decipher the evolution of the mercury-methylating gene, hgcAB, constrain the ancestral origin of the hgc operon, and explain the distribution of hgc in Bacteria and Archaea. We infer the extent to which vertical inheritance and horizontal gene transfer have influenced the evolution of mercury methylators and hypothesize that evolution of this trait bestowed the ability to produce an antimicrobial compound (MeHg + ) on a potentially resource-limited early Earth. We speculate that, in response, the evolution of MeHg + -detoxifying alkylmercury lyase (encoded by merB) reduced a selective advantage for mercury methylators and resulted in widespread loss of hgc in Bacteria and Archaea.